Comparison of Cytokine Expression in Paediatric and Adult Psoriatic Skin - Jin Cheol Kim; So Min Kim; Byung Woo Soh; Eun-So Lee (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)